POLYBIO: Multimodal Biometric Data Acquisition Platform and Security System - Kounoudes, Anastasis; Tsapatsoulis, Nicolas; Milis, Marios; Theodosiou, Zenonas (My University, 2008)
Biometrics is the automated method of recognizing a person based on a physiological or behavioural characteristic. Biometric technologies are becoming the foundation of an extensive array of highly secure identification and personal verification solutions. In the last few years there is increasing evidence that technologies based on multimodal biometrics can provide better identification results if proper fusion schemes are accommodated. In this work, we present a novel platform for multimodal biometric acquisition which combines voice, video, fingerprint and palm photo acquisition through an integrated device, and the preliminary fusion experiments on combining the acquired biometrics modalities. The results are encouraging and show clear improvement both in terms of False Acceptance Rate and False Rejection Rates compared to the corresponding single modality approaches. In the current report, fusion was accommodated at the output of the single modalities; however, fusion experimentation is ongoing and further fusion methodologies are under investigation.
Keywords: Biometric identification--Congresses